Benthic community descriptions at underwater peaks in McMurdo Sound, Antarctica. (8th March 2022) - Kim, Stacy; Cazenave, François
Abstract: In McMurdo Sound, Antarctica, fine-scale bathymetry is poorly defined, and benthic communities at water depths over 30 m have not been well described. We describe the benthic communities on two previously unknown bathymetric highs, sampled in 2012 and 2014, using scuba divers, a remotely operated vehicle, and a specially designed time-lapse camera system (SeeStar). One site (Mystery Peak) was capped by a dense thicket of the sponge Homaxinella balfourensis, a temporally variable community that likely formed in response to iceberg disturbance. Below the H. balfourensis cap (at 40 m) and at the second site (Tongue Peak, 70 m), the communities conformed to a known ecological pattern driven by food availability from benthic diatoms. Overall, mixed hydroids and bryozoans were the dominant organisms, and at greater depths the sponge Rosella podagrosa also became abundant. Over time, there were only minor changes in these communities on isolated bathymetric highs. Ice is a physical factor that interacts with depth and influences benthic communities through disturbance by icebergs and anchor ice, and through food supply by sea ice coverage. The SeeStar time-lapse camera system performed exceptionally and opens up opportunities for new winter observations in the Antarctic.